Analisis Penggunaan Media Pembelajaran Berbasis Video Animasi dalam Pembelajaran Ilmu Pengetahuan Sosial Siswa Sekolah Dasar - anisa zahro; Mellia Nor Halifah; Rafika Siyami Qodriyah; Surya Adam Zainu Nasrullah; Fina Fakhriyah; Nur Fajrie (Jurnal Inovasi Pendidikan dan Ilmu Sosial, 2024)
This study aims to analyzing of using animated video-based learning media in learning Social Studies (IPS) for grade IV students at SDN 3/4 Margoyoso. Using a qualitative research method with a narrative approach, data was collected through observation and interviews to get an in-depth picture of classroom conditions and the learning process. The results showed that the use of animated videos as learning media was able to increase students' enthusiasm and learning spirit. This media makes it easier for students to understand abstract concepts in social studies material, especially related to the map of Indonesia, in a more interesting and interactive way. In addition, the use of animated videos has a significant effect on increasing students' knowledge in social studies learning. In conclusion, the application of animated video-based learning media makes a significant positive contribution to increasing students' knowledge and involvement in the learning process.